The complete mitochondrial genome of Hemerobius japonicus (Neuroptera: Hemerobiidae) - Yang Zhao; Heping Shao; Ningning Zhang; Jinquan Jing (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Hemerobius japonicus Nakahara, was sequenced in this study. The complete mitochondrial genome is a typical double-stranded circular molecule of 18,585 bp (GenBank accession number: MN852445), containing 37 typical animal mitochondrial gene and an A + T-rich region. The gene order is identical to that of the putative ancestral arrangement of insects and other lacewings. 13 protein-coding genes (PCGs) possessed common triplet initiation codons ATN except ND1 possessed TTG and mostly terminated with TAN codons except for ND5 and ND4 with a single T residue adjacent to a downstream tRNA gene. All of the 22 tRNAs, ranging from 63 to 72 bp, can be folded into classic clover-leaf secondary structure except for tRNASer(AGN), in which the dihydrouridine (DHU) arm did not form a stable stem-loop structure. The control region is 1416 bp long with an A + T content of 90.3%. In the sampled families of Neuroptera, each family showed a monophyletic cluster and Polystoechotidae + Rapismatidae, Osmylidae + the remaining families, Hemerobiidae + (Chrysopidae + (Polystoechotidae + Rapismatidae)) are recovered in phylogenetic analyses with high supports.